Activity of Compounds on Seaweed Eucheuma cottonii Extract as Antioxidant Candidate to Prevent Effects of Free Radical in Water Pollution - Dewi Wulandari; Yuni Kilawati; Mohamad Fadjar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
Water pollution can make many problems such as, the incidence of disease and poisoning. Pollution in water can produce free radicals and it is can trigger of disease for aquatic organisms. There is some efforts that can be done to provide this problem, such as chemical compound that can reduce the reaction of free radicals. Antioxidants are one of the chemical compounds that can reduce the activity of free radicals. Eucheuma cottonii is the one of a seaweed that has many in antioxidant compounds, such as phenol compounds, but it is also rich in iodine fiber and other important minerals. The method used in this research is descriptive explorative and experimental method. This research was conducted with several stages of seaweed extraction. Identification of Eucheuma cottonii extract is using FTIR test. The last stage is an antioxidant activity test that includes DPPH test (1,1-diphenyl-2-picrilhidrazil) and Inhibition Concentration 50 (IC 50). The results obtained in this study were based on FTIR test of antioxidant compound in Eucheuma cottonii seaweed extract. The one of compounds that have antioxidant activity include galaktosa-4-sulfat. Based on the results of antioxidant activity test using DPPH obtained that seaweed extract Eucheuma cottonii active as an antioxidant to ward off free radicals in the waters. The concentration of Eucheuma cottonii seaweed extract for preventive 50% concentration of DPPH is 39,926 ppm.